Black artists in America from civil rights to the bicentennial - Bernier, Celeste-Marie 1975-; Jenkins, Earnestine; Simone, Alaina (Dixon Gallery and Gardens, 2023)
"Black Artists in America: From Civil Rights to the Bicentennial explores African American art during the turbulence of the 1950s, 1960s, and 1970s. The catalogue considers the various ways in which African American artists responded to growing civil unrest, challenging the cultural, environmental, political, racial, and social issues of the era. In the 1960s, Black artists who came of age during World War II and the increasing civil rights activity of the 1950s continued to challenge inequities in the art world. They created works that celebrated their racial identity, communicated with Black audiences, and participated in the struggle for political, economic, and social equality. The establishment of artist collectives such as Spiral and museums devoted to Black art, including the Studio Museum in Harlem, alongside the emergence of art historians and critics like David Driskell and Linda Goode Bryant, marked early steps to bring Black art into broader artistic discourse. In addition to 140 full-color images of approximately seventy paintings, sculptures, and works on paper from public and private collections across the country, the catalogue features in-depth essays, including original research on artists James Porter and Merton Simpson"--
Impressum: This publication was produced in conjunction with the exhibition "Black Artists in America: From Civil Rights to the Bicentennial", on view at the Dixon Gallery and Gardens, Memphis, October 22, 2023 - January 14, 2024, and at the Crocker Art Museum, Sacramento, February 4 - May 19, 2024
Keywords: Simpson, Merton Daniel -- 1928-2013; Porter, James A. -- 1905-1970; Geschichte 1950-1980; Schwarze; Künstler; Künstlerin; Kunst; USA; African American art / 20th century / Exhibitions; Porter, James A. / (James Amos) / 1905-1970 / Exhibitions; Simpson, Merton D. / (Merton Daniel) / 1928-2013 / Exhibitions; Art noir américain / 20e siècle / Expositions; ART / American / African American & Black; ART / American / General; Ausstellungskatalog -- Dixon Gallery and Gardens -- 22.10.2023-14.01.2024 -- Memphis, Tenn.; Ausstellungskatalog -- Crocker Art Museum -- 04.02.2024-19.05.2024 -- Sacramento, Calif.